Methodological considerations in implementing the WHO Global Survey for Monitoring Maternal and Perinatal Health - Archana Shah; Anibal Faundes; M'Imunya Machoki; Vicente Bataglia; Faouzi Amokrane; Allan Donner; Kidza Mugerwa; Guillermo Carroli; Bukola Fawole; Ana Langer; Jean José Wolomby; Alberto Naravaez; et al. (Bulletin of the World Health Organization)
OBJECTIVE: To set up a global system for monitoring maternal and perinatal health in 54 countries worldwide. METHODS: The WHO Global Survey for Monitoring Maternal and Perinatal Health was implemented through a network of health institutions, selected using a stratified multistage cluster sampling design. Focused information on maternal and perinatal health was abstracted from hospital records and entered in a specially developed online data management system. Data were collected over a two- to three-month period in each institution. The project was coordinated by WHO and supported by WHO regional offices and country coordinators in Africa and the Americas. FINDINGS: The initial survey was implemented between September 2004 and March 2005 in the African and American regions. A total of 131 institutions in seven African countries and 119 institutions in eight Latin American countries participated. CONCLUSION: This project has created a technologically simple and scientifically sound system for large-scale data management, which can facilitate programme monitoring in countries.